2017
DOI: 10.5901/jesr.2017.v7n1p151
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of Algebraic-Geometrical Duality in Shaping Fraction’s Meaning and Calculation Strategies with Fractions

Abstract: Many mathematical concepts and processes, besides the algebraic form of their presentation, can be modeled as well geometrically through diagrams and graphics. Both these aspects of concepts demonstration (algebraic and geometrical aspect) are present on mathematical textbooks of pre-university education. In this paper we consider algebraic and geometrical aspect on 6 th grade math textbooks and in particular algebraic-geometrical duality, aiming that the fraction concept and the fraction calculation strateg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…Among the different mathematical contents, one interesting element is the study of fractions due to, among other reasons, their importance in the learning of several science areas. Students possess the knowledge that allows them to represent fractions, establish equivalences and operate with them, but they do not identify the meaning of the mathematical procedures involved, a situation that is fundamental for a deep and lasting learning of fractions [59,60]. Furthermore, the research on preservice teachers' conceptual knowledge of fraction showed that from the five sub-constructs considered, the participants were most successful with part-whole, presenting little knowledge of the rest [37].…”
Section: Discussionmentioning
confidence: 99%
“…Among the different mathematical contents, one interesting element is the study of fractions due to, among other reasons, their importance in the learning of several science areas. Students possess the knowledge that allows them to represent fractions, establish equivalences and operate with them, but they do not identify the meaning of the mathematical procedures involved, a situation that is fundamental for a deep and lasting learning of fractions [59,60]. Furthermore, the research on preservice teachers' conceptual knowledge of fraction showed that from the five sub-constructs considered, the participants were most successful with part-whole, presenting little knowledge of the rest [37].…”
Section: Discussionmentioning
confidence: 99%
“…There are three forms of abstraction which are; the empirical abstraction where the focus is on the objects properties and knowledge on the object derives from his own properties, the pseudo-empirical abstraction where the focus is on actions which leaves out the properties that the action of the subjects have introduced into objects and reflective abstraction where further constructions can then be accomplished by its existing structures used to construct new structures [4].…”
Section: Introductionmentioning
confidence: 99%